Effects of Concomitant Benzodiazepines and Antidepressants Long-Term Use on Social Decision-Making: Results From the Ultimatum Game - Fernandes, Carina; Garcez, Helena; Balaban, Senanur; Barbosa, Fernando; Pereira, Mariana R.; Silveira, Celeste; Marques-Teixeira, João; Gonçalves, Ana R. (Frontiers in Psychology, 2022)
Benzodiazepines and antidepressants have been shown to change responses to unfairness, however the effects of their combined use on unfairness evaluation are unknown. This study examines the effects of concomitant benzodiazepines and antidepressants long-term use on the evaluation of fair and unfair offers. To analyze behavioral changes on responses to unfairness, we compared the performance of medicated participants and healthy controls in the Ultimatum Game (UG), both in the proposer and in the respondent role. The results showed that long-term psychotropic users had the worse economic strategy by accepting less offers than control subjects. However, in the proposer role, the unfair offers made by participants were similar between groups. The present results suggest that long-term use of psychotropic medication, specifically the combination of benzodiazepines and antidepressants, may increase the sensitivity to unfairness, resulting in higher rejection rates in conditions where this strategy is the most disadvantageous.